1975
DOI: 10.1152/ajplegacy.1975.229.2.394
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise on lipoprotein lipase activity in rat heart and skeletal muscle

Abstract: Lipoprotein lipase activity was measured in the three skeletal muscle fiber types of untrained rats and in those of rats subjected to a 12-wk program of treadmill running. Lipoprotein lipase activity in slow-twitch red fibers was approximately 14- to 20-fold higher (P less than 0.001) than that in fast-twitch white and approximately 2-fold higher (P less than 0.001) than that in fast-twitch red fibers in the untrained animals. These results suggest that, in sedentary animals, mainly slow-twitch red and fast-tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

1977
1977
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(31 citation statements)
references
References 0 publications
1
29
0
1
Order By: Relevance
“…Of interest, however, the Pima Indians in this study tended to have an increase rather than decrease in SMLPL after insulin administration. Perhaps this response helps to meet the fuel need ofmuscle in the setting ofinsulin resistance (31 Since a reduced proportion oftype I, high-oxidative muscle fibers has been implicated in the etiology of obesity ( 14) and both animal and human studies have established the relationship between muscle fiber type and muscle LPL activity (15)(16)(17)(18), SMLPL activity would be predicted to be low before or during the development ofthe obese state. In the study ofTaskinen et al (32), SMLPL was lower in obese subjects, whereas Reitman et al (33) found no difference between lean and obese.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of interest, however, the Pima Indians in this study tended to have an increase rather than decrease in SMLPL after insulin administration. Perhaps this response helps to meet the fuel need ofmuscle in the setting ofinsulin resistance (31 Since a reduced proportion oftype I, high-oxidative muscle fibers has been implicated in the etiology of obesity ( 14) and both animal and human studies have established the relationship between muscle fiber type and muscle LPL activity (15)(16)(17)(18), SMLPL activity would be predicted to be low before or during the development ofthe obese state. In the study ofTaskinen et al (32), SMLPL was lower in obese subjects, whereas Reitman et al (33) found no difference between lean and obese.…”
Section: Resultsmentioning
confidence: 99%
“…Wade et al ( 14) showed that the combustion of FA during light exercise is related to muscle fiber-type proportions. It is also recognized, from studies in both humans and animals, that muscle LPL activity is higher in muscles composed predominantly of high-oxidative slow twitch fibers and low in muscle with greater content of low-oxidative fast twitch fibers (15)(16)(17)(18). We hypothesized that a high 24-h RQ, i.e., a low fat/CHO oxidation ratio, is associated with low skeletal muscle LPL activity.…”
mentioning
confidence: 99%
“…In animals, the results have been inconsistent. Borensztajn et al (23) found a significant increase of LPL activity with exercise in tissue homogenates of all fiber types of skeletal muscle. In contrast, other investigators were unable to find any difference in LPL activity of either muscle or adipose tissue between trained and sedentary rats (24)(25)(26).…”
Section: Discussionmentioning
confidence: 97%
“…feeding/ fasting [4], cold adaptation [5], physical exercise [6,7], lactation [8] and infections/tumours [9]. Hormones involved in the regulation include insulin, catecholamines, glucocorticoids and tumour necrosis factor (reviewed in refs.…”
Section: Introductionmentioning
confidence: 99%